2011
DOI: 10.1002/jcb.23021
|View full text |Cite
|
Sign up to set email alerts
|

Euphorbia factor L1 reverses ABCB1‐mediated multidrug resistance involving interaction with ABCB1 independent of ABCB1 downregualtion

Abstract: Euphorbia factor L1 (EFL1) belongs to diterpenoids of genus Euphorbia. In this article, its reversal activity against ABCB1-mediated MDR in KBv200 and MCF-7/adr cells was reported. However, EFL1 did not alter the sensitivity of KB and MCF-7 cells to chemotherapeutic agents. Meanwhile, EFL1 significantly increased accumulation of doxorubicin and rhodamine 123 in KBv200 and MCF-7/adr cells, showing no significant influence on that of KB and MCF-7 cells. Furthermore, EFL1 could enhance the ATP hydrolysis activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
(36 reference statements)
0
23
0
Order By: Relevance
“…In several studies (Jiao et al, 2015; Zhang et al, 2013; Zhang et al, 2011) using human tumor MDR cells, compounds 1 and 3 , as well as analogues of 3 , have exhibited MDR reversal ability. Compounds 2 and 3 were suggested to act as modulators of P-gp, as both compounds could stimulate P-gp ATPase activity (Duan et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In several studies (Jiao et al, 2015; Zhang et al, 2013; Zhang et al, 2011) using human tumor MDR cells, compounds 1 and 3 , as well as analogues of 3 , have exhibited MDR reversal ability. Compounds 2 and 3 were suggested to act as modulators of P-gp, as both compounds could stimulate P-gp ATPase activity (Duan et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Cancer chemotherapy offers effective treatment and developing novel anticancer drugs is a promising strategy to overcome cancer [ 28 , 29 ]. More and more evidence suggests that the success of anti-tumor chemotherapy depends on the discovery and development of novel drugs [ 23 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As part of ongoing research, we have exhaustively investigated Caper Euphorbia Seed, examining the chemical isolation and structure identification of its components and their pharmacological aspects [ 20 , 21 , 22 , 23 ]. During these studies, lathyrol-3-phenylacetate-5,15-diacetate (deoxy Euphorbia factor L1, DEFL1) was isolated from Caper Euphorbia Seed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used for thousands of years for the treatment of warts and tumors [17], antibacterial activity [18], antiviral [19,20], anti-in ammation activity [21,22], anti-proliferative, antitumor-promoting and apoptosis inducing activities [23][24][25], and et al The main compounds of the ES include Lathyrane-type, diterpenoids, Ingenane-type, diterpenoids, Coumarins, etc. Many studies have been found that Euphorbia diterpenes can be regarded as effective lead compounds for the reversal of MDR [26][27][28]. It can be seen that ES have certain development value.…”
Section: Introductionmentioning
confidence: 99%